Luteolin-Rich Extract from Harrisonia perforata (Blanco) Merr. Root Alleviates SARS-CoV-2 Spike Protein-Stimulated Lung Inflammation via Inhibition of MAPK/NLRP3 Inflammasome Signaling Pathways - Warathit Semmarath; Punnida Arjsri; Kamonwan Srisawad; Sonthaya Umsumarng; Pornngarm Dejkriengkraikul (Life)
The COVID-19-related long-standing effect or Post-Acute Sequelae of COVID-19 (PASC) is often associated with NLRP3 inflammasome activation in pulmonary inflammation elicited by SARS-CoV-2 spike proteins. Spike proteins engage toll-like receptors (TLRs) in respiratory epithelial cells, leading to excessive cytokine production. Given the need for effective therapeutic strategies to mitigate spike protein-stimulated lung inflammation, we examined the anti-inflammatory properties of luteolin and ethanolic extract from Harrisonia perforata (Blanco) Merr. root. The ethanolic extract of H. perforata root (HPEE) contained a high concentration of luteolin flavonoid (143.53 ± 1.58 mg/g extract). Both HPEE (25–100 μg/mL) and luteolin (4.5–36 μM) significantly inhibited inflammation stimulated by the Wuhan (W) and Omicron (O) spike protein S1, as evidenced by a dose-dependent significant decrease in IL-6, IL-1β, and IL-18 secretion in A549 lung epithelial cells (p < 0.05). Furthermore, pretreatment with HPEE or luteolin prior to spike protein exposure (100 ng/mL) significantly, in a dose-dependent manner, repressed the inflammatory mRNA expression (p < 0.05). Mechanistic study revealed that HPEE and luteolin suppressed NLRP3 inflammasome signaling activation by reducing their machinery protein expressions. Additionally, they inhibited the ERK/JNK/p38 MAPK signaling activation, resulting in decreased inflammatory mRNA expression and cytokine release. These findings suggest that H. perforata root extract and its major flavonoid luteolin exert potent anti-inflammatory effects and may offer therapeutic potential against spike protein-induced lung inflammation.